Evaluation of the holographic parameters by electrosynthesized CdXZn1−XS (X=0.3) thin films using double exposure digital holographic interferometry technique. (February 2017) - Dhaygude, H.D.; Chikode, P.P.; Shinde, S.K.; Shinde, N.S.; Fulari, V.J.
Abstract: In this paper, we have reported the optical non destructive technique, which uses double exposure digital holographic interferometry (DEDHI) together with simple mathematical interpretation, which instantly situates to the thickness of thin films, deposited mass, stress to substrate and fringe width for different deposition times. Here, the stainless steel substrate was exposed for different intervals of time. It is observed that the fringe width, stress to substrate changes with changing the time of deposition. This effect is due to the increase in thickness of CdX Zn1−X S (X=0.3) thin films. Thus, holographic studies show sensitivity to deposition time and concentrations of solution. Graphical abstract: Highlights: Surface deformation study using DEDHI technique. Deposition time increases, the thickness increases and stress decreases. Deposition time increases, mass increases with decreasing the fringe width.